Anti-beta2-glycoprotein I IgG antibodies are associated with early-onset cryptogenic ischemic stroke - Jaakonmäki, Nina; Helin, Tuukka; Szanto, Timea; Zedde, Marialuisa; Sarkanen, Tomi; Martinez-Majander, Nicolas; Sinisalo, Juha; Junttola, Ulla; Redfors, Petra; von Sarnowski, Bettina; Waje-Andreassen, Ulrike; Ylikotila, Pauli; et al. (SAGE PUBLICATIONS LTD, 2026)
Background: Previously undetected antiphospholipid antibodies (aPLs) potentially provide explanations for early-onset cryptogenic ischemic stroke (CIS). Prior association studies conducted over a decade ago were inconclusive and not focused on patients with CIS.
Methods: SECRETO is a multi-center case-control study enrolling patients aged 18-49 years with imaging-positive acute CIS and 1:1 matched stroke-free controls. Lupus anticoagulant (LA), anticardiolipin (aCL), and anti-beta2-glycoprotein I (aβ2GPI) IgG antibodies were assessed from blood samples taken at two time points (baseline and 12-weeks) from patients and at a single time point from controls. Conditional logistic regression models assessed the association of aPLs, adjusted for age, level of education, and vascular risk factors.
Results: A total of 503 patient-control pairs were analyzed. At either time-point, compared to healthy controls, patients had more frequently positive aβ2GPI (patients 11.9% vs controls 2.0%, p < 0.001). There was no significant difference in the presence of positive LA between patients and controls. In the logistic regression model, at either time-point positive aB2GI and aCL were associated with CIS (odds ratio [OR] 11.22, 95% confidence interval [CI] 4.35-28.95 and OR 20.85, 95% CI 204-213.16, respectively). The frequency of patients with positive aβ2GPI or aCL increased from baseline to 12 weeks (p < 0.001), whereas frequency of positive LA results decreased (p < 0.001).
Conclusions: Positive aβ2GPI and aCL, but not LA, detected either shortly after stroke or after 12 weeks were associated with early-onset CIS. Notably, after the acute phase, frequencies of positive aβ2GPI and aCL increased, whereas LA showed a reverse trend.